Commentary: Advocating for patient and public involvement and engagement in health economic evaluation - Staniszewska, Sophie; Jakab, Ivett; Low, Eric; Mossman, Jean; Posner, Phil; Husereau, Don; Stephens, Richard; Drummond, Michael (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Patient and public involvement in health economic evaluation is still relatively rare, compared to other areas of health and social care research. Developing stronger patient and public involvement in health economic evaluation will be important in the future because such evaluations can impact on the treatments and interventions that patients can access in routine care. Main text The Consolidated Health Economic Evaluation Reporting Standards (CHEERS) is a reporting guideline for authors publishing health economic evaluations. We established an international group of public contributors who were involved in the update of the CHEERS 2022 reporting guidance, ensuring two items (areas of reporting) specifically about public involvement were included. In this commentary we focus on the development of a guide to support public involvement in reporting, a key suggestion made by the CHEERS 2022 Public Reference Group, who advocated for greater public involvement in health economic evaluation. This need for this guide was identified during the development of CHEERS 2022 when it became apparent that the language of health economic evaluation is complex and not always accessible, creating challenges for meaningful public involvement in key deliberation and discussion. We took the first step to more meaningful dialogue by creating a guide that patient organisations could use to support their members to become more involved in discussions about health economic evaluations. Conclusions CHEERS 2022 provides a new direction for health economic evaluation, encouraging researchers to undertake and report their public involvement to build the evidence base for practice and may provide some reassurance to the public that their voice has played a part in evidence development. The CHEERS 2022 guide for patient representatives and patient organisations aims to support that endeavour by enabling deliberative discussions among patient organisations and their members. We recognise it is only a first step and further discussion is needed about the best ways to involve public contributors in health economic evaluation.

Plain language abstract Background Patient and public involvement in health economic evaluation is still relatively rare, compared to other areas of health and social care research. Developing stronger patient and public involvement in health economic evaluation will be important in the future because such evaluations can impact on the treatments and interventions that patients can access in routine care. Main text We established an international group of public contributors who were involved in the development of the CHEERS 2022 reporting guidance, ensuring two items (areas of reporting) specifically about patient and public involvement were included. In this commentary we focus on the development of a guide to support patient and public involvement in reporting, a key suggestion made by the CHEERS 2022 Public Reference Group, who advocated for greater public involvement in health economic evaluation. The need for this guide was identified during the development of CHEERS 2022 when it became apparent that the language of health economic evaluation is complex and not always accessible, creating challenges for meaningful public involvement in key deliberation and discussion. We took the first step to more meaningful dialogue by creating a guide that patient representatives and patient organisations could use as support to become more involved in discussions about health economic evaluations. Conclusions CHEERS 2022 provides a new direction for health economic evaluation, encouraging researchers to undertake and report their public involvement in order to build the evidence base for practice. The CHEERS 2022 guide aims to support patient representatives and patient organisations to become more involved in discussions about health economic evaluations. We recognise it is only a first step and further discussion is needed about the best ways to involve public contributors in health economic evaluation.